Advances in Hurricane Research Modelling, Meteorology, Preparedness and Impacts - Hickey, Kieran (IntechOpen, 2012)
This book provides a wealth of new information, ideas and analysis on some of the key unknowns in hurricane research. Topics covered include the numerical prediction systems for tropical cyclone development, the use of remote sensing methods for tropical cyclone development, a parametric surface wind model for tropical cyclones, a micrometeorological analysis of the wind as a hurricane passes over Houston, USA, the meteorological passage of numerous tropical cyclones as they pass over the South China Sea, simulation modelling of evacuations by motorised vehicles in Alabama, the influence of high stream-flow events on nutrient flows in the post hurricane period, a reviews of the medical needs, both physical and psychological of children in a post hurricane scenario and finally the impact of two hurricanes on Ireland. Hurricanes discussed in the various chapters include Katrina, Ike, Isidore, Humberto, Debbie and Charley and many others in the North Atlantic as well as numerous tropical cyclones in the South China Sea.